Sequential Serratia liquefaciens and Serratia odorifera Pneumonia in an Elderly Patient with ARDS and Septic Shock: A Case Report - Aditya Kafi Amrullah; Syarifuddin; Reza Gusni S (The Indonesian Journal of General Medicine, 2026)
Background: Acute respiratory distress syndrome (ARDS) in the elderly is frequently precipitated by nosocomial pneumonia and complicated by sepsis and cardiac comorbidity. While Serratia marcescens is a recognized pathogen, pneumonia due to non-marcescens Serratia (e.g., S. liquefaciens, S. odorifera) is exceptionally rare. Antimicrobial stewardship—with early broad empiric therapy followed by de-escalation—may reshape respiratory microbiology during prolonged ICU care. Case Presentation: A 78-year-old man with hypertension and remote pulmonary tuberculosis presented with 3 days of progressive dyspnea and epigastric chest pain radiating to the right arm, plus diaphoresis. On arrival: RR 42/min, HR 105/min, BP 50/30 mmHg, SpO₂ 57% (room air). Chest radiographs showed bilateral alveolar infiltrates; he was intubated and ventilated (PSIMV, FiO₂ 100%, PEEP 5 cmH₂O) with persistent severe hypoxemia consistent with ARDS. Initial labs revealed leukocytosis, elevated CRP, D-dimer 430 ng/mL FEU, anemia, hypokalemia, and variable glycemia; ionized calcium was repeatedly low (0.97–1.05 mmol/L). He developed recurrent SVT with RBBB (rates up to ~200 bpm) requiring amiodarone and bisoprolol. Empiric meropenem (1 g IV q8h) was started. Sputum culture on day 2 grew Serratia liquefaciens. Following antimicrobial adjustment, a repeat culture on day 7 yielded S. odorifera with an AmpC-like resistance pattern (non-susceptible to early-generation cephalosporins/aminopenicillins; susceptible to cefepime / carbapenem / fluoroquinolone / TMP-SMX).Therapy was tailored to levofloxacin 750 mg IV daily plus cefoperazone 1 g IV q12h. Blood cultures remained negative; GeneXpert MTB/RIF was negative. Tracheostomy on ICU day 5 enabled weaning (PSV→CPAP→T-piece 10→5 L/min) with SpO₂ 96–99%. Doppler later showed right popliteal artery stenosis; heparin was escalated to therapeutic dosing. By ICU day 14, he was clinically improved and transferred to the ward. Conclusion: This case illustrates sequential pneumonia due to two rare non-marcescens Serratia species in severe ARDS, emphasizing careful microbiologic reassessment during stewardship-driven therapy and the value of targeted antibiotics plus multidisciplinary ICU care.